STUDY OF ESTABLISHMENT OF SPECIAL ECONOMIC ZONES OF TOURISM OF ROTE NDAO REGENCY - Donny Teguh Santoso Junias Meyulinda Aviana Elim Raden Setyo Budi Suharto (JAKA - Jurnal Jurusan Akuntasi, 2018)
The purpose of this study is to analyze the readiness of the Special Economic Zone of Tourism through regional strategic factors and mapping of tourist destination areas in Rote Ndao Regency. Regional development policy is an important instrument in overcoming regional problems, optimizing regional potential, reducing regional disparities, accelerating regional development, increasing regional competitiveness and excellence and improving the welfare of local communities. The data analysis technique uses descriptive qualitative analysis method with an exploratory approach. The results showed that Rote Ndao Regency was considered ready to be a Special Economic Zone of Tourism in terms of the aspects of the tourism industry and other strategic aspects such as infrastructure facilities and local human resources. Commitment and high synergy between the central government, Rote Ndao Regency government, local communities, the private sector, and foreign support will accelerate regional development to optimize regional excellence and improve national competitiveness.